Risk Factors Associated With Bordetella pertussis Among Infants ⩽4 Months of Age in the Pre-Tdap Era: United States, 2002–2005. Issue 8 (August 2017) - Curtis, Christine Robinette; Baughman, Andrew L.; DeBolt, Chas; Goodykoontz, Susan; Kenyon, Cynthia; Watson, Barbara; Cassiday, Pamela K.; Miller, Claudia; Pawloski, Lucia C.; Tondella, Maria-Lucia C.; Bisgard, Kristine M.
Abstract : Background: In the United States, infants have the highest reported pertussis incidence and death rates. Improved understanding of infant risk factors is needed to optimize prevention strategies. Methods: We prospectively enrolled infants ⩽4 months of age with incident-confirmed pertussis from 4 sites during 2002–2005 (preceding pertussis antigen-containing vaccination recommendations for adolescents/adults); each case-patient was age and site matched with 2 control subjects. Caregivers completed structured interviews. Infants and their contacts ≥11 years of age were offered serologic testing for IgG; being seropositive was defined as ≥94 antipertussis toxin IgG enzyme-linked immunosorbent assay units per milliliter. Results: Enrolled subjects (115 case-patients; 230 control subjects) had 4396 contacts during incubation periods; 83 (72%) case-patients had ≥1 contact with prolonged (≥5 days) new cough in primary or secondary households. In multivariable analysis, the odds for pertussis were higher for infants with primary/secondary household contacts who had a prolonged new cough, compared with infants who did not. These contacts included mother [adjusted matched odds ratio (aMOR), 43.8; 95% confidence interval (CI), 6.45–298.0] and ≥1 nonmother contact (aMOR, 20.1; 95% CI, 6.48–62.7). Infants receiving breast milk with 0–1 formula feedings daily had decreased pertussis odds (aMOR, 0.27; 95% CI, 0.08–0.89), compared with those receiving more formula. Of 41 tested case-patients, 37 (90%) were seropositive. Conclusions: Pertussis in infants was associated with prolonged new cough (≥5 days) in infants' household contacts. Findings suggest that breastfeeding protects against pertussis and warrants recommendation with pertussis prevention strategies, which currently include pertussis vaccination of pregnant mothers and infants' close contacts.